Fluorescence resonance energy transfer for investigation of the interaction of Para Red with serum albumins. (14th July 2015) - Zhu, Lin; Zeng, Xiaodan; Zhang, Fusheng
Abstract: Para Red (PR) has been isolated from food additives, and shown to be toxic to humans. To facilitate examination of its toxicity, the interaction between PR and serum albumins (SA) was studied using fluorescence quenching and circular dichroism (CD) spectrophotometry. The experiments showed that the fluorescence intensity of serum albumins decreased with increasing concentrations of PR, which resulted from the binding of PR and SA. The binding constant, number of binding sites and thermodynamic parameters were calculated and hydrogen bond and van der Waals interactions were shown to play a key role in the binding process. Competition experiments indicated that PR mainly binds to Trp residues of SA within the site I. As the CD and three‐dimensional spectra revealed, the addition of PR induced a conformational change in SA. Copyright © 2015 John Wiley & Sons, Ltd.